Method for preparing porous phosphorus-carbon composite material and application of porous phosphorus-carbon composite material in sodium-ion battery

By using sugarcane to prepare fiber porous carbon and red phosphorus, the porous phosphorus-carbon composite material is prepared as the negative electrode of the sodium ion battery, and the problems of poor conductivity and volume expansion of the negative electrode material in the sodium ion battery are solved, and better cycling performance and capacity are achieved.

CN119706793AInactive Publication Date: 2025-03-28SHENZHEN BAK POWER BATTERY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411902815.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The lack of suitable negative electrode materials in sodium ion batteries leads to poor conductivity and volume expansion problems, limiting their application.

Method used

Sugar cane is used as the source of fiber porous carbon and combined with red phosphorus to prepare a porous phosphorus-carbon composite material. By using this material as the negative electrode of a sodium ion battery, the fiber mesh structure is used to improve conductivity and restrict the volume expansion of phosphorus.

Benefits of technology

The better circulation performance and higher capacity of sodium ion batteries are achieved, which improves the conductivity of the material and slows down the capacity attenuation caused by volume expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706793A_ABST
    Figure CN119706793A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, particularly relates to a method for preparing a porous phosphorus-carbon composite material and application of the porous phosphorus-carbon composite material in a sodium ion battery, and provides the following scheme aiming at the problems that a material capable of being applied to a sodium battery negative electrode is urgently found and the application of the material is limited by conductivity and volume expansion in the prior art. The method comprises the following steps: S1, preparing fiber porous carbon: removing moisture from sugarcane in a drying oven, crushing the sugarcane, soaking the crushed sugarcane in absolute ethyl alcohol, centrifuging, drying, and keeping the temperature of a solid at 1000 DEG C for 4 hours; s2, preparing a crude product of the phosphorus-carbon composite material: uniformly mixing red phosphorus and fiber porous carbon, preserving heat at 700 DEG C for 4 hours, preparing a fiber porous carbon base by using sugarcane as a carbon source, constraining volume expansion of phosphorus during charging and discharging, and being beneficial to obtaining higher capacity and better cycle performance compared with porous carbon without phosphorus doping; the problem of poor conductivity of the phosphorus-carbon material can be solved by the fibrous reticular compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a method for preparing a porous phosphorus-carbon composite material and an application thereof in a sodium ion battery. Background Art

[0002] The Chinese patent document with application number 201210256056.4 discloses a lithium-ion battery, which is formed in an environment of -20 to 60°C by the following steps: the lithium-ion battery after injection and infiltration is subjected to pulse constant current charging until the voltage reaches a specified value, the specified value range of the voltage is 3.4-4.2V; the lithium-ion battery is subjected to constant voltage charging until the current reaches a specified value, the specified value of the current is 0.05C; the lithium-ion battery is subjected to constant current discharge, the discharge voltage value range is 3.0-2.0V, and the discharge current value range is 0.01-2.0C. The silicon-carbon material negative electrode lithium-ion battery provided by the present invention adopts a pulse constant current charging formation method, which can effectively slow down the battery volume expansion, and the battery deformation, pole piece cracking, and pole piece wrinkling caused by the volume expansion, thereby slowing down the capacity decay.

[0003] However, there are also some problems with lithium-ion batteries. For example, sodium-ion batteries are expected to become a substitute for lithium batteries because of their familiar mechanisms with lithium-ion batteries and abundant sodium resources. The radius of sodium ions is larger than that of lithium ions. For this reason, the structure of negative graphite commonly used in lithium batteries will be destroyed when used in sodium batteries, making it difficult to exert its performance. It is urgent to find materials that can be used in sodium electronegative electrodes. Red phosphorus is the most promising sodium electronegative electrode, which can contribute a capacity of 2596mAh g-1 at a potential of about 0.4V. However, its low conductivity and 400% volume expansion during deintercalation limit its application. Combining red phosphorus with carbon-based materials is the easiest way to solve the above problems. On the one hand, carbon materials can be used as electron transfer paths, and on the other hand, the volume expansion problem during ion deintercalation can be alleviated. In order to solve the above-mentioned discharge problem, the present application provides a fibrous porous carbon-phosphorus-carbon composite material, which is applied to sodium ion batteries with good cycle performance and high capacity. Summary of the invention

[0004] Based on the background technology, there is an urgent need to find materials that can be used at the sodium electronegative level, but the conductivity and volume expansion limit their application. The present invention proposes a method for preparing a porous phosphorus-carbon composite material and its application in a sodium ion battery.

[0005] A method for preparing a porous phosphorus-carbon composite material proposed by the present invention comprises the following steps:

[0006] S1: Preparation of fibrous porous carbon: After removing water from sugarcane in an oven, the sugarcane was crushed, soaked in anhydrous ethanol, centrifuged and dried, and the solid was kept at 1000°C for 4 hours;

[0007] S2: Preparation of crude phosphorus-carbon composite material: red phosphorus and fibrous porous carbon were mixed evenly and then kept at 700°C for 4 hours, and then kept at 280°C for 40 hours;

[0008] S3: Preparation of phosphorus-carbon composite materials: The crude phosphorus-carbon composite material is washed with CS2 and dried to obtain a porous phosphorus-carbon composite material. Sugarcane is used as a carbon source to prepare a fibrous porous carbon matrix. On the one hand, it restrains the volume expansion of phosphorus during charge and discharge, which is beneficial for obtaining higher capacity and better cycle performance compared to non-phosphorus-doped porous carbon. On the other hand, the fibrous network compound is beneficial for improving the poor conductivity of phosphorus-carbon materials.

[0009] Preferably, in S1, the method for preparing sugarcane includes obtaining sugarcane stalks, removing leaves from the sugarcane stalks, cutting off the roots and tops of the sugarcane stalks, then cleaning them, drying them, peeling them, and finally cutting them into several sections and chopping them into small pieces to obtain sugarcane raw materials for subsequent processing.

[0010] Preferably, the sugarcane raw material can also be selected from the discarded bagasse after sugar extraction in the sugar industry, which is the sugarcane fiber residue remaining after sugar extraction after peeling, and can improve the comprehensive utilization rate of the material.

[0011] Preferably, in S1, the sugarcane is placed in a 120° C. forced air drying oven for 45 hours to remove moisture from the sugarcane, and then crushed into powder. The powder is soaked in anhydrous ethanol, and the solid is centrifuged and dried to enhance the drying effect. The anhydrous ethanol can be used to activate the sugarcane powder to facilitate subsequent carbonization.

[0012] Preferably, in S1, the solid is kept warm in a tubular furnace filled with N2 atmosphere, and the heating rate is controlled at 5°C / min until the temperature reaches 1000°C, followed by keeping warm for 4 hours, so that fibrous porous carbon can be obtained, which is convenient for heating, and the N2 atmosphere can provide protection to ensure the carbonization effect.

[0013] Preferably, in S2, the weight ratio of red phosphorus and fibrous porous carbon is controlled at: 1-3:2-4, the red phosphorus and fibrous porous carbon are mixed and added to ethanol, mixed and stirred for 2 hours, poured into a centrifugal device for dehydration, and dried in a vacuum drying oven at 60°C to obtain a mixed solid. The ratio of red phosphorus and fibrous porous carbon is convenient for subsequent reactions, and ethanol facilitates the dissolution and mixing of red phosphorus and fibrous porous carbon, which is convenient for subsequent processing.

[0014] Preferably, the mixed solid is heated to 700°C at a heating rate of 5°C / min, kept at 280°C for 40 hours and then cooled to room temperature at a cooling rate of 2°C / min, so as to obtain a crude product of a phosphorus-carbon composite material, which is convenient for the reaction of the material.

[0015] Preferably, in S2, during the process of keeping the temperature at 280°C for 40 hours, white phosphorus will be converted into red phosphorus. The material contains some white phosphorus, and the high temperature can convert the white phosphorus into red phosphorus as much as possible.

[0016] Preferably, in S3, the crude phosphorus-carbon composite material needs to be washed three times with CS2 to remove the white phosphorus therein; during drying, it is dried in a vacuum drying oven at 80°C for 8 hours, which can effectively remove the white phosphorus and facilitate the subsequent use of the material.

[0017] A method for preparing porous phosphorus-carbon composite materials and its application in sodium ion batteries, NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3Mn 1 / 3 O2 was used as the positive electrode of sodium battery, a porous phosphorus-carbon composite material with a phosphorus content of 40% was used as the negative electrode, and a ceramic single-sided coating was used as the diaphragm to prepare the roll core. 8.0g of liquid was injected, and after overnight room temperature rest, pre-charging, high-temperature aging, and capacity division, 0.5C charging and 1C discharge cycle performance tests were carried out.

[0018] Beneficial effects of the present invention:

[0019] 1. Use sugarcane as a source of fibrous porous carbon and combine it with red phosphorus to prepare phosphorus-carbon composites;

[0020] 2. Sugarcane compounds as a carbon source combined with red phosphorus to prepare fibrous porous phosphorus-carbon composites;

[0021] Using sugarcane as a carbon source to prepare fibrous porous carbon substrates, on the one hand, restrains the volume expansion of phosphorus during charging and discharging, which is beneficial for obtaining higher capacity and better cycle performance compared to non-phosphorus-doped porous carbon. On the other hand, the fibrous network compound is beneficial for improving the poor conductivity of phosphorus-carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The working flow diagram proposed for the present invention;

[0023] Figure 2 The charge-discharge curve of the 20% porous phosphorus-carbon composite material proposed by the present invention when applied to sodium battery;

[0024] Figure 3 The 20% porous phosphorus-carbon composite material proposed by the present invention has a 0.5C charge and 1C discharge cycle performance when applied to sodium battery;

[0025] Figure 4 Impedance comparison between the 20% porous phosphorus-carbon composite material proposed in the present invention and undoped red phosphorus. DETAILED DESCRIPTION

[0026] The present invention will be further explained below in conjunction with specific embodiments.

[0027] Reference Figure 1-4 , Embodiment 1

[0028] This embodiment proposes a method for preparing a porous phosphorus-carbon composite material and an application in a sodium ion battery, comprising the following steps:

[0029] S1: impurity removal: the sugarcane was placed in a forced air drying oven at 120°C for 45 hours to remove moisture, then crushed into powder, soaked in anhydrous ethanol, centrifuged and dried;

[0030] S2: Preparation of fibrous porous carbon: The dried powder was heated to 1000 °C at a rate of 5 °C / min in a tube furnace under N2 atmosphere and kept at this temperature for 4 h;

[0031] S3: Preparation of crude phosphorus-carbon composite material: Red phosphorus and fibrous porous carbon were mixed in ethanol at a ratio of 2:3, stirred for 2 hours, and then centrifuged to obtain a mixed solid. After drying in a vacuum drying oven at 60°C, the uniformly mixed solid was heated to 700°C at a rate of 5°C / min and kept warm for 4 hours, and then kept warm at 280°C for 40 hours to convert white phosphorus into red phosphorus as much as possible, and then cooled to room temperature at a rate of 2°C / min to obtain a crude product of three-dimensional fibrous porous carbon material;

[0032] S4: Preparation of phosphorus-carbon composite material: The crude three-dimensional fiber porous carbon material was washed three times with CS2 to remove white phosphorus, and dried in a vacuum drying oven at 80° C. for 8 hours to obtain a porous phosphorus-carbon composite material;

[0033] S5: NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2 was used as the positive electrode of sodium battery, the porous phosphorus-carbon composite material with a phosphorus content of 40% obtained above was used as the negative electrode, and the ceramic single-sided coating was used as the diaphragm to prepare the roll core. 8.0g of liquid was injected, and after overnight room temperature rest, pre-charging, high-temperature aging, and capacity division, 0.5C charging and 1C discharge cycle performance tests were carried out.

[0034] Reference Figure 1-4 , Embodiment 2

[0035] This embodiment proposes a method for preparing a porous phosphorus-carbon composite material and an application in a sodium ion battery, comprising the following steps:

[0036] S1: Impurity removal: Sugarcane was placed in a drying oven at 120°C for 45 hours to remove moisture, then crushed into powder, soaked in anhydrous ethanol, centrifuged and dried;

[0037] S2: Preparation of fibrous porous carbon: The dried powder was heated to 1000°C at 5°C / min in a tube furnace under N2 atmosphere and kept at this temperature for 4 hours;

[0038] S3: Preparation of crude phosphorus-carbon composite material: Red phosphorus and fibrous porous carbon were mixed in ethanol at a mass ratio of 3:2, stirred and centrifuged to obtain a mixed solid, dried in a vacuum drying oven at 60°C, and the uniformly mixed solid was heated to 700°C at 5°C / min and kept at this temperature for 4 hours, and kept at 280°C for 40 hours, and then cooled to room temperature at a rate of 2°C / min to obtain a crude product of three-dimensional fibrous porous carbon material;

[0039] S4: Preparation of phosphorus-carbon composite material: The crude three-dimensional fiber porous carbon material was washed with CS2 for 3 times, and dried in a vacuum drying oven at 80° C. for 8 hours to obtain a porous phosphorus-carbon composite material;

[0040] S5: NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2 was used as the positive electrode of sodium battery, the above-mentioned porous phosphorus-carbon composite material with a phosphorus content of 60% was used as the negative electrode, and the ceramic single-sided coating was used as the diaphragm to prepare the roll core. 8.0g of liquid was injected, and after overnight room temperature rest, pre-charging, high-temperature aging, and capacity division, 0.5C charging and 1C discharge cycle performance tests were carried out.

[0041] Reference Figure 1-4 , Embodiment 3

[0042] This embodiment proposes a method for preparing a porous phosphorus-carbon composite material and an application in a sodium ion battery, comprising the following steps:

[0043] S1: Impurity removal: Sugarcane was placed in a drying oven at 120°C for 45 hours to remove moisture, then crushed into powder, soaked in anhydrous ethanol, centrifuged and dried;

[0044] S2: Preparation of fibrous porous carbon: The dried powder was heated to 1000°C at 5°C / min in a tube furnace under N2 atmosphere and kept at this temperature for 4 hours;

[0045] S3: Preparation of crude phosphorus-carbon composite material: Red phosphorus and fibrous porous carbon were mixed in ethanol at a mass ratio of 1:4, stirred and centrifuged to obtain a mixed solid, dried in a vacuum drying oven at 60°C, and the uniformly mixed solid was heated to 700°C at 5°C / min and kept at this temperature for 4 hours, and then kept at 280°C for 40 hours, and then cooled to room temperature at a rate of 2°C / min to obtain a crude product of three-dimensional fibrous porous carbon material;

[0046] S4: Preparation of phosphorus-carbon composite material: The crude three-dimensional fiber porous carbon material was washed with CS2 for 3 times, and dried in a vacuum drying oven at 80° C. for 8 hours to obtain a porous phosphorus-carbon composite material;

[0047] S5: NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2 was used as the positive electrode of sodium battery, the porous phosphorus-carbon composite material with a phosphorus content of 20% obtained above was used as the negative electrode, and the ceramic single-sided coating was used as the diaphragm to prepare the roll core. 8.0g of liquid was injected, and after overnight room temperature rest, pre-charging, high-temperature aging, and capacity division, 0.5C charging and 1C discharge cycle performance tests were carried out.

[0048] Reference Figure 1-4 , Comparative Example 1

[0049] The following steps are involved:

[0050] S1: impurity removal: the sugarcane was placed in a forced air drying oven at 120°C for 45 hours to remove moisture, then crushed into powder, soaked in anhydrous ethanol, centrifuged and dried;

[0051] S2: Preparation of fibrous porous carbon: The dried powder was heated to 1000 °C at a rate of 5 °C / min in a tube furnace under N2 atmosphere and kept at this temperature for 4 h;

[0052] S3: NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2 is used as the positive electrode of sodium battery, the above-mentioned porous fiber carbon material is used as the negative electrode, and the ceramic single-sided coating is used as the diaphragm to prepare the roll core. 8.0g of liquid is injected. After overnight room temperature rest, pre-charging, high-temperature aging, and capacity division, 0.5C charging and 1C discharge cycle performance tests are carried out.

[0053] Comparison of cyclic performance of phosphorus-carbon materials with different phosphorus contents

[0054]

[0055] It can be seen from the above table that phosphorus doping has a significant improvement on capacity. Compared with the porous fiber carbon not doped with red phosphorus, the first discharge capacity is uniformly improved, and the porous fiber carbon doped with red phosphorus has a higher capacity retention rate in sodium battery.

[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a porous phosphorus-carbon composite material, characterized in that: The following steps are involved: S1: Preparation of fibrous porous carbon: After removing water from sugarcane in an oven, the sugarcane was crushed, soaked in anhydrous ethanol, centrifuged and dried, and the solid was kept at 1000°C for 4 hours; S2: Preparation of crude phosphorus-carbon composite material: red phosphorus and fibrous porous carbon were mixed evenly and then kept at 700°C for 4 hours, and then kept at 280°C for 40 hours; S3: Preparation of phosphorus-carbon composite material: The crude phosphorus-carbon composite material obtained is washed with CS2 and dried to obtain a porous phosphorus-carbon composite material.

2. A method for preparing a porous phosphorus-carbon composite material according to claim 1, characterized in that: In S1, the method for preparing sugarcane includes obtaining sugarcane stalks, removing leaves from the sugarcane stalks, cutting off the roots and tops of the sugarcane stalks, washing them, drying them, peeling them, and finally cutting them into several sections and chopping them into small pieces to obtain sugarcane raw materials.

3. A method for preparing a porous phosphorus-carbon composite material according to claim 2, characterized in that: Sugarcane raw materials can also be selected from the discarded bagasse after sugar extraction in the sugar industry, which is the sugarcane fiber residue remaining after sugar extraction after peeling.

4. The method for preparing a porous phosphorus-carbon composite material according to claim 1, characterized in that: In S1, the sugar cane is placed in a forced air drying oven at 120° C. for 45 hours to remove moisture from the sugar cane, and then crushed into powder. The powder is soaked in anhydrous ethanol, and the solid is obtained by centrifugation and dried.

5. The method for preparing a porous phosphorus-carbon composite material according to claim 1, characterized in that: In S1, the solid is kept warm in a tubular furnace filled with N2 atmosphere, and the heating rate is controlled at 5°C / min until the temperature reaches 1000°C, followed by keeping warm for 4 hours to obtain fibrous porous carbon.

6. The method for preparing a porous phosphorus-carbon composite material according to claim 1, characterized in that: In S2, the weight ratio of red phosphorus to fibrous porous carbon is controlled at 1-3:2-4. The red phosphorus and fibrous porous carbon are mixed and added to ethanol, mixed and stirred for 2 hours, poured into a centrifugal device for dehydration, and dried in a vacuum drying oven at 60° C. to obtain a mixed solid.

7. A method for preparing a porous phosphorus-carbon composite material according to claim 6, characterized in that: The mixed solid is heated to 700°C at a heating rate of 5°C / min, kept at 280°C for 40 hours, and then cooled to room temperature at a cooling rate of 2°C / min to obtain a crude phosphorus-carbon composite material.

8. The method for preparing a porous phosphorus-carbon composite material according to claim 1, characterized in that: In S2, during the 40-hour heat preservation at 280°C, white phosphorus is converted into red phosphorus.

9. The method for preparing a porous phosphorus-carbon composite material according to claim 1, characterized in that: In S3, the crude phosphorus-carbon composite material product needs to be washed three times with CS2 to remove the white phosphorus therein; when drying, it is dried in a vacuum drying oven at 80° C. for 8 hours.

10. An application of the method for preparing a porous phosphorus-carbon composite material according to claim 1 in a sodium ion battery, characterized in that: NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2 was used as the positive electrode of sodium battery, porous phosphorus-carbon composite material as the negative electrode, and ceramic single-sided coating as the diaphragm to prepare the roll core. 8.0g of liquid was injected, and after overnight room temperature rest, pre-charging, high-temperature aging, and capacity division, 0.5C charging and 1C discharge cycle performance tests were carried out.

Citation Information

Patent Citations

  • Lithium ion battery

    CN102820487B

  • Lithium-sulfur battery composite cathode material, preparation method thereof and application of lithium-sulfur battery

    CN108666537A

  • Phosphorus-based negative electrode material and preparation method thereof, negative electrode and lithium ion battery

    CN109216682A

  • Self-supporting cotton biomass carbon loaded red phosphorus sodium ion battery negative electrode material and preparation method thereof

    CN116759582A

  • Preparation method and application of dual-carbon modified red phosphorus composite material

    CN119029178A